Representasi Makna Bahasa Cinta Pada Game Otome Love and Deepspace - Cahyani Nadia; Ricky Widyananda Putra (Kartala Virtual Studies, 2026)
One way to achieve a quality romantic relationship is through effective communication. Language is a key element in the communication process, playing a crucial role in strengthening a relationship. In the context of romantic relationships, there is the concept of love languages, which explains that each individual has different preferences in receiving and expressing love and their feelings. One medium that illustrates love languages ​​is the digital game Otome Love and Deepspace, which presents a visual romantic experience. Based on this, the researcher is interested in examining how the representation of love languages ​​is displayed in visual and narrative form in the game Otome Love and Deepspace. The researcher used a qualitative method with a Roland Barthes semiotic analysis approach, which includes the interpretation of denotation, connotation, and myth formation. The results show that there are five love languages ​​represented in the game and provide an ideal picture of how women want to be loved and understood emotionally.